Implementation of Distance Learning Policy In The Era of The Covid-19 Pandemic In Banjar District, South of Kalimantan - Jamaluddin Jamaluddin; Suriansyah Umar; Alma Rajab; Haitami Haitami (International Journal of Politic, Public Policy and Environmental Issues, 2021)
In its implementation, the Banjar Regency Government, in particular the Education and Culture Office, has not fully implemented the policy of the Minister of Education and Culture regarding Distance Learning, so it is interesting to examine some of the obstacles to its implementation, including in the context of the economic condition of the community. For this reason, it is essential to do this research, especially in high school (SMA), where many students already have a means of communication in the form of mobile phones. The main objective of the study is to describe the policy implementation model owned by the Education Office in Banjar Regency based on the economic conditions of the people in Banjar Regency and a description of the implementation of distance learning policies in terms of communication aspects, sources of resources, tendencies, and implementing bureaucracy. This study uses a qualitative research approach, namely research that seeks to understand and present the phenomena around teaching and learning activities in senior high schools in Banjar Regency, selected based on each school's public and private categories. The schools selected were High School 2 Martapura and High School Darul Hijrah Cindai Alus, Banjar Regency. To obtain accurate data and information, the selected research informants are the Head of the Banjar Regency Education Office, the Principal or his representative at SMA 2 Martapura, and SMA Darul Hijrah Cindai Alus Banjar. The school students are represented by five people from each school and the student's parents. The projected results of this study are expected to help enrich public policy knowledge, especially regarding policy implementation by the latest developments and conditions of technology development, information especially the Covid-19 pandemic era, and submitting criticism and suggestions, especially for the development of education in Banjar Regency.